2014
DOI: 10.1080/02755947.2014.943863
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Annuli Formation in Pectoral Fin Rays from Shovelnose Sturgeon in the Lower Platte River, Nebraska

Abstract: Fish age is commonly estimated by counting bands on calcified structures. Age estimates are used to calculate information on population dynamics such as growth, mortality, and recruitment. Pectoral fin rays are the most frequently used structure to age sturgeon species, yet little work has been done to validate annuli formation. We collected Shovelnose Sturgeon Scaphirhynchus platorynchus monthly from the lower Platte River, Nebraska, during 2011 and 2012 and removed the leading, left pectoral fin ray from eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…We found blue sucker fin rays difficult to age above 10 years, and we lack confidence in the accuracy of many of our older ages. For shovelnose sturgeon, marginal increment analysis of fin rays indicated that features on the ray that were perceived as annuli did not necessarily correspond to true annual growth marks, suggesting that age estimates from fin rays might be inaccurate (Ruggs, Hamel, Pegg, & Hammen, ). If that is the case, then all ages of shovelnose sturgeon (and perhaps blue sucker as well) are in question.…”
Section: Discussionmentioning
confidence: 99%
“…We found blue sucker fin rays difficult to age above 10 years, and we lack confidence in the accuracy of many of our older ages. For shovelnose sturgeon, marginal increment analysis of fin rays indicated that features on the ray that were perceived as annuli did not necessarily correspond to true annual growth marks, suggesting that age estimates from fin rays might be inaccurate (Ruggs, Hamel, Pegg, & Hammen, ). If that is the case, then all ages of shovelnose sturgeon (and perhaps blue sucker as well) are in question.…”
Section: Discussionmentioning
confidence: 99%
“…Presumed fin ray "annuli" were not congruent with age assignments, and estimates of growth from back-calculated estimates were overestimated. In addition, Rugg et al (2014) used marginal increment analysis in an attempt to validate annual growth mark deposition of shovelnose sturgeon fin rays from the Platte River, Nebraska. Annuli were found to be inconsistently deposited on fin rays, and the presence of closely spaced or false annuli was prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…Size at first reproduction was similar between the lower Platte River and the Missouri River for both females and males and less than values reported for the Mississippi and Wabash rivers (Table ). Age at first reproduction was similarly younger in the lower Platte River (Table ); a caveat to this result, however, is that recent research has shown that fin rays do not provide reliable age estimates (Hamel, ; Hamel et al., ; Rugg et al., ). However, Hamel et al.…”
Section: Discussionmentioning
confidence: 73%